Effect of terminal heat stress on stay-green and senescence process could explain genetic variation in grain yield and nutritional profile in wheat (Triticum aestivum L.) - Lekhana, M. V.; Meena, Rajesh Kumar; Anirudh, T. V.; Barman, Mainak; Kumar, Abhishek; Reddy, M. S. Sai; Sharma, Amit Kumar; Rajeev, Nayan Bahuguna; Singh, Satish Kumar (Springer, 2025)
Wheat is a staple food crop for the majority of the world’s population. Heat stress affects reproductive development, seed-set and seed weight, eventually reducing yield and total biomass in wheat. Stay-green contributes to seed weight by allowing more assimilate partitioning to grain. Conversely, senescence is essential for the recycling of nutrients to developing grain. We have studied a set of 26 high-yielding wheat genotypes to study the effect of terminal heat stress on the stay-green and senescence process to explain genetic variation and trade-off associated between grain yield and grain nutrients under field conditions. Our results revealed that heat stress accelerated the senescence process and significantly reduced average grain filling duration by 8 days. The negative effect of heat stress on spikelet fertility and seed weight resulted in reduced grain yield (25%). On the contrary, a positive influence of heat was observed on grain protein (6–21%), grain minerals, and reduced C:N ratio. Interestingly, genotype (HTWYT42) with a longer stay-green period, showed higher yield under heat stress, whereas genotype (HTWYT43) showed early onset but a slower pace of senescence accumulating more grain protein, minerals and lower C:N ratio under heat stress. This study demonstrates a strong trade-off between grain yield and nutrition. However, maintaining an optimum balance between stay-green and a slower rate of senescence could be crucial to minimizing this trade-off, and achieving both higher yield and improve grain nutrition. Furthermore, understanding the mechanisms underlying slower senescence in source tissues could be essential for developing wheat genotypes with enhanced grain nutrient content.